Implementation of Earth Structure Learning Applications Using Markerless Augmented Reality Using Surface Tracking Method - Saepulrohman, Asep; Zuraiyah, Tjut Awaliyah; Prastio, Agung Dwi (JOURNAL OF SCIENCE EDUCATION AND PRACTICE, 2023)
In science lessons at school there are materials that are taught, one of which is a lesson about the layers of the earth. As an alternative learning media, Augmented Reality technology is needed which can help teachers have a variety of learning media, so that they can accommodate the learning needs of students who have various types of learning characteristics. In this study the authors made augmented reality using markerless so that they could display or show how the structure of the earth's layers looks like seeing directly without markers or markers. Using EasyAR as a Software Development Kit (SDK) because it has many features and methods that can be used for creating augmented reality.